Answer:
-5x^2-2x
Step-by-step explanation:
When distributing, you multiply the term outside the brackets to all the terms in brackets.
If the term outside the bracket is negative, then when distributing/opening the brackets, the signs of the terms changes.
So in this prob. -x would multiply to both +5x and +2
-x*5x+-x*2
∴-5x^2-2x
Answer:
(x -6)^2 +(y -3)^2 = 2
Step-by-step explanation:
The midpoint (C) is the center of the circle:
C = ((5, 4) +(7, 2))/2 = ((5+7)/2, (4+2)/2) = (6, 3)
A circle with center (h, k) that goes through point (a, b) can be written as ...
(x -h)^2 +(y -k) ^2 = (a -h)^2 +(b -k)^2
Using the values for this problem, we get ...
(x -6)^2 +(y -3)^2 = (5 -6)^2 +(4 -3)^2
(x -6)^2 +(y -3)^2 = 2
Answer:
207,50
Step-by-step explanation:
1% = 2,5
2,5x25 = 62,5 250 - 62,5 = 187,5
2,5x8 = 20
187,5+20= 207,50
Answer:
(x−1)(x+6)(2x+7); 2x+7
Step-by-step explanation:
2x3+17x2+23x−42
=(x−1)(x+6)(2x+7)
i could just simplify the first part